Mitigations risk of trademark rights law as credit bank guarantee - Prasastinah Usanti, Trisadini (IUS ET SCIENTIA, 2020)
The Efforts to minimize legal risk over brand certificate guarantees in banking practices by conducting a professional analysis of brands. The main thing that is done by the bank is to identify whether the rights to the mark meet the legal and economic requirements as a guarantee and the important is imposition of perfect pawn collateral institutions or fiduciaries then it cause the property rights is born and bank domiciled as a preferred creditor. The analysis on guarantee is the bank effort to ward off legal risk such as weakness of the alliance until not fulfilled the contractual terms or not perfect of collateral binding even the cancellation of the brand certificate. If this is not mitigated, it will be detrimental to the position of the bank as a creditor because the bank is only located as a concurrent creditor.